ANALISIS KESULITAN BELAJAR MATA PELAJARAN MATEMATIKA - Purwanto, Farich (Universitas Islam Zainul Hasan Genggong, 2024)
To prepare students to be able to apply mathematics and mathematical thinking patterns in everyday life and in studying various sciences at school, the difficulties in understanding mathematics subject matter experienced by students, especially in elementary schools, need to be addressed immediately. This research aims to analyze the difficulties experienced by grade 3 students at MI Izzul Islam. This research is a type of descriptive research with a qualitative approach, the data collection techniques used are observation, interviews and documentation. Data validation techniques use technical triangulation, source triangulation and time triangulation. The research was carried out in class 3 at MI Izzul Islam, Kamalkuning Village, Krejengan District, Probolinggo Regency. The results of the research show that mathematics is a subject that is considered difficult by the majority of grade 3 students at MI Izzul Islam, especially regarding the operations of multiplication and division. This is caused by various factors originating from internal and external factors.